1996
DOI: 10.1111/j.1365-2826.1996.tb00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol, Progesterone, and Prolactin Regulate Maternal Nest‐Building in Rabbits

Abstract: Maternal nest-building in rabbits, expressed across the last third of pregnancy, consists of: digging a burrow, collecting straw and shaping it into a nest inside the burrow, plucking body hair and lining the straw nest with it. The sequential expression of these activities is correlated with specific changes in the plasma concentration of estradiol, progesterone (P), and prolactin (PRL). To further substantiate the participation of these hormones in the control of maternal nest-building we explored in ovariec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 34 publications
3
40
0
2
Order By: Relevance
“…These results suggest that cortisol is not involved in the regulation of nest building but may be influenced by external factors such as environment. Although there is evidence for progesterone being involved in aspects of nest building regulation in rabbits (González-Mariscal et al 1996) and straw carrying in pigs (Castren et al 1993), the present experiments have not shown any relationship between plasma progesterone and nest building.…”
Section: Discussionmentioning
confidence: 36%
See 1 more Smart Citation
“…These results suggest that cortisol is not involved in the regulation of nest building but may be influenced by external factors such as environment. Although there is evidence for progesterone being involved in aspects of nest building regulation in rabbits (González-Mariscal et al 1996) and straw carrying in pigs (Castren et al 1993), the present experiments have not shown any relationship between plasma progesterone and nest building.…”
Section: Discussionmentioning
confidence: 36%
“…Prolonged high levels of peripheral oestradiol and progesterone increase nest building behaviour in rabbits, and circulating prolactin also exerts an influence (González-Mariscal et al 1996). However, manipulation of peripheral concentrations of neither oestradiol (Burne et al 1999) nor prolactin (Boulton et al 1998) affect nest building in the pig.…”
Section: Introductionmentioning
confidence: 99%
“…Como se observa en la Figura 1.A, la excavación del sustrato se incrementa conforme se avanza en la gestación, es decir, con altas concentraciones de estradiol 17-β y de progesterona y declina hacia final de la misma, cuando disminuyen los niveles de progesterona. Estas variaciones se replican al inyectar a conejas ovariectomizadas benzoato de estradiol 17-β y progesterona (González-Mariscal et al, 1996). El acarreo de paja al interior del nido se observa solamente al declinar la concentración sanguínea de progesterona al final de la gestación o al dejar de administrar esta hormona a conejas ovariectomizadas tratadas con benzoato de estradiol 17-β (Figura 1.B).…”
Section: Mecanismos Hormonales Que Regulan El Comportamiento Materno unclassified
“…Sin embargo, el brusco incremento en la con-Figura 1. Variaciones en la intensidad de las conductas de excavación (panel A) y de acarreo de paja (panel B) a lo largo de la gestación (González-Mariscal et al 1994) o durante la administración, a conejas ovariectomizadas (ovx), de benzoato de estradiol (días 1-22; 5 µg/día) combinado con 2 ó 10 mg/día de progesterona (P; días 3-16; González-Mariscal et al 1996).…”
Section: Mecanismos Hormonales Que Regulan El Comportamiento Materno unclassified
See 1 more Smart Citation